Study of finish milling of titanium alloy (TI6AL4V). (2016) - Krishnaraj, V.; Krishna, B. Hari; Sheikh-Ahmad, Jamal Y.
End milling experiments on titanium alloy (Ti6Al4V) using carbide insert-based cutting tool were carried out under dry cutting conditions on a CNC machining centre. The cutting speeds selected for the experiments were between 20 and 50 m min −1 and feed rates were from 0.02 to 0.08 mm/tooth, while the axial depth of cut was kept constant at 1.0 mm. For the range of cutting speeds and feeds, measurements of cutting forces, surface roughness and cutting temperature were performed. From the experimental study, it was found that cutting speed of 30 m min −1 and feed rate of 0.02 mm/tooth could be used for machining Ti alloy because of lower cutting forces. Moreover it is found that cutting speed has significant effect on temperature when compared to feed/tooth. Micro hardness beneath the machined surface has been measured and found that it is a function cutting force and temperature. Tool life of the cutting insert is also found at the optimal cutting speed.